Pengaruh Media Visual Terhadap Konsentrasi Belajar Siswa Matapelajaran PKN di Kelas 2 SDN 176 Pekanbaru - Febrillaa, Cindy; Rahmi, Laili; Lingga, Leny Julia (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to determine whether there is an influence of visual media on the learning concentration of PKN students in grade 2 SDN 176 Pekanbaru. This research is a type of Pre-Experimental Design research, with a One-Group Pretest-Posttest research design. The population in this study were all grade 2 students at SDN 176 Pekanbaru. The sample of this research is class 2B students, totaling 24 students at SDN 176 Pekanbaru. Determination of the sample using purposive sampling technique. The results showed that through the t test (paired test) with a significance level of 5%, the t count was -6.868 with a significance level of 0.000. From the results of these calculations, it can be said that the t count is -6.868 with a significance of 0.000 <5%. So it can be concluded that the use of visual media in Civics lesson content has a significant influence on the learning concentration of grade 2 students at SDN 176 Pekanbaru